Concomitant variability in high-latitude aerosols, water isotopes and the hydrologic cycle. Issue 11 (November 2018) - Markle, Bradley; Steig, Eric; Roe, Gerard; Winckler, Gisela; McConnell, Joseph
Abstract The interpretation of ice-core records rests on understanding the processes affecting trace constituents of the atmosphere that are preserved in ice. Stable-isotope ratios of ice are widely used as a palaeothermometer, an interpretation backed by well-established theory. In contrast, the interpretation of aerosols such as mineral dust and sea salts has remained a topic of debate. Here, we demonstrate that both the fractionation of water isotopes and the scavenging of aerosols are fundamentally driven by the same process, the condensation of water from the atmosphere. Water isotope ratios and aerosol concentrations in ice cores are remarkably coherent on all timescales longer than a few centuries. This shared low-frequency variability is dominated by the essential physics of the hydrologic cycle, which also accounts for the difference in variability between marine- and terrestrial-sourced aerosols in ice cores, as well as the global spatial pattern of aerosol changes recorded in both marine sediments and ice. These results have implications for past changes in radiative forcing and other fundamental aspects of climate, such as polar amplification, which are imprinted on the relationships between these proxy records. On timescales of centuries and longer, aerosol concentrations in Antarctic ice are controlled by changes in the nature of mid- and high-latitude precipitation, according to analyses of palaeoclimate data.